Penatalaksanaan infeksi Candida tropicalis pada penderita median rhomboid glossitis The management of infection of Candida tropicalis at median rhomboid glossitis patient - Cane Lukisari; Kus Harijanti (Journal of Dentomaxillofacial Science, 2011)
Oral candidiasis is oral mucosal infectious caused by Candida albicans or non-candida albicans candida (NCAC).Each Candida species infection has same clinical manifestation, the different only in invasive nature and antifungiresponse. C.tropicalis is most virulence NCAC because the most adherence ability to epithelial cells in vitro as wellas medium level proteinase secretion. In addition, C.topicalis is the second most common colony on human. A studyreported of C.tropicalis as causa of 16% hospitalized oral candidiasis, anti fungal drugs and systemic antibioticwas known as trigger factors. This paper report and discuss oral candidiasis due to C.tropicalis in patient, adultmale, with median rhomboid glossitis. The patient also used broad spectrum antibiotic and topical corticosteroidwith imprecise dose. The management of this case was terminated antibiotic and corticosteroid, oral hygieneoptimalization and was given 0.25% chlorhexidine gluconate. However, oral hygiene optimalization, predispositionfactors elimination, and, precise therapy would give a good prognosis.